Human capital and economic activity in urban America - Jaison R. Abel; Todd M. Gabe (Federal Reserve Bank of New York, 2008)
We examine the relationship between human capital and economic activity in U.S. metropolitan areas, extending the literature in two ways. First, we utilize new data on metropolitan area GDP to measure economic activity. Results show that a one-percentage-point increase in the proportion of residents with a college degree is associated with about a 2 percent increase in metropolitan area GDP per capita. Second, we develop measures of human capital that reflect the types of knowledge within U.S. metropolitan areas. Regional knowledge stocks related to the provision of producer services and information technology are important determinants of economic vitality.
Keywords: R11; J24; O40; 330; Human capital; knowledge; new economy; productivity; Humankapital; Bildungsabschluss; Sozialprodukt; Produktivität; Stadt; USA